2006
DOI: 10.1017/s0967199406003649
|View full text |Cite
|
Sign up to set email alerts
|

Increase in DNA fragmentation and apoptosis-related gene expression in frozen-thawed bovine blastocysts

Abstract: SummaryEvaluation of apoptosis and expression level of apoptosis-related genes is useful for examining the variation in embryo quality according to environmental change. The objective of this study was to investigate DNA fragmentation and apoptosis-related gene expression patterns in frozen-thawed bovine blastocysts.In vitroproduced day 7 blastocysts were frozen by two different vitrification methods (conventional 0.25 ml straw or MVC straw). After thawing, DNA fragmentation of surviving embryos was examined b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
56
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(66 citation statements)
references
References 29 publications
5
56
0
2
Order By: Relevance
“…In this study, there was a 2.4-fold increase (P < 0.0001) in the apoptosis rate of vitrified (49.4 ± 1.9) in relation to fresh embryos (20.8 ± 1.1). Similar apoptosis profiles were observed in other studies, which demonstrated increases of 3.7-fold (Park et al, 2006) and 1.7-fold (Márquez-Alvarado et al, 2004) in the apoptosis rate of cryopreserved embryos compared with fresh embryos.…”
Section: Cryopreservation Of Bovine Embryossupporting
confidence: 87%
“…In this study, there was a 2.4-fold increase (P < 0.0001) in the apoptosis rate of vitrified (49.4 ± 1.9) in relation to fresh embryos (20.8 ± 1.1). Similar apoptosis profiles were observed in other studies, which demonstrated increases of 3.7-fold (Park et al, 2006) and 1.7-fold (Márquez-Alvarado et al, 2004) in the apoptosis rate of cryopreserved embryos compared with fresh embryos.…”
Section: Cryopreservation Of Bovine Embryossupporting
confidence: 87%
“…The expression pattern of development and/or apoptosis related genes reflects embryo quality [2,24,25]. BIRC5 (survivin) is important for optimal embryo development and it suppresses apoptosis in preimplantation embryos [25].…”
Section: Discussionmentioning
confidence: 99%
“…BIRC5 (survivin) is important for optimal embryo development and it suppresses apoptosis in preimplantation embryos [25]. Although HSPA1A is a constitutive gene in embryos, its expression level is linked to the response to cellular stress [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the period of post fertilization culture environment can have a significant impact on mRNA abundance (Lonergan et al, 2003b). Moreover, the survival of an embryo in a specific culture system can be done by monitoring the levels of mRNA and this could an indirect way of quality assessment in the embryo & Park et al,2006. This further generate information on expression patterns used as genetic markers and gives an indication of abnormal embryo during their preimplantation stages.…”
Section: Cx43glut1 G6pdmentioning
confidence: 99%